Role and position of Indonesian Medical Disciplinary Honour Council: fair medical dispute resolution - Khalif Ardi, Muhammad; Laksito, FX Hastowo Broto; Laurent, Andriamalala (Journal of Law, Environmental and Justice, 2023)
The main aim of this study is to offer a detailed account of the role and status of the Medical Ethics Council of Indonesia (MKDKI) in promoting the fair resolution of medical disputes in Indonesia. This study is a form of normative legal research. The research findings suggest that MKDKI should be the designated authority for resolving medical disputes since it has the requisite expertise in applying professional discipline in the medical domain. Moreover, MKDKI is a reputable organization assessing whether a physician has breached professional disciplinary norms. The phrase "can" in Article 66 paragraph (1) of Law Number 29 of 2004 governing Medical Practice includes the option to file a complaint against MKDKI or choose not to do so. Legal ambiguity may arise, requiring substituting the term "can" with "must." Consequently, all grievances related to medical matters must be addressed exclusively through MKDKI as an obligatory measure. Conducting a judicial review of Article 66, paragraph (1) of Law Number 29 of 2004 regarding Medical Practice is essential. Furthermore, it is crucial to consider the jurisdiction of the Medical Council of Indonesia (MKDKI) in establishing compensation for parties involved in disputes. For the sake of legal precision for both medical professionals and the general population, every decision made by the MKDKI (Medical Knowledge and Decision-making Institute) must be thoroughly evaluated.